Implementation of Fuzzy Logic Controller in Three Area Multi Source LFC System - Sriram Vivek, B; Swetha, K; Vijaya Kumar, D (International Journal of Engineering and Technology, 2018)
The objective of this paper is to analyze power system with is interconnected with neighboring areas and having multisource power generation which is equipped with the fuzzy logic controller. Thermal, hydro and gas generating stations is used in each control area by considering real power environment. The proposed controller is tested with sudden step load disturbances. The dynamic response of LFC problem is studied by comparing with conventional controllers using MATLAB simulink software and found dynamic responses obtained satisfy the LFC requirement.